2015
DOI: 10.1140/epjc/s10052-015-3375-z
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of higher-dimensional anisotropic compact star

Abstract: We provide a new class of interior solutions for anisotropic stars admitting conformal motion in higherdimensional noncommutative spacetime. The Einstein field equations are solved by choosing a particular density distribution function of Lorentzian type as provided by Nazari and Mehdipour [1,2] under a noncommutative geometry. Several cases with 4 and higher dimensions, e.g. 5, 6, and 11 dimensions, are discussed separately. An overall observation is that the model parameters, such as density, radial pressure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 49 publications
(94 reference statements)
4
54
0
Order By: Relevance
“…It is interesting to note that all the data fall within the observed range of the corresponding star's physical parameters [12,22,31,[44][45][46][47]. It would be interesting to perform a comparative study with the data of our Table 3 with that of Table 4 of Maurya et al [25] where they have prepared the table for the value of n = 3.3 only for different compact stars whereas in the present study our table includes a wide range of n = 3 to n = 10,000.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is interesting to note that all the data fall within the observed range of the corresponding star's physical parameters [12,22,31,[44][45][46][47]. It would be interesting to perform a comparative study with the data of our Table 3 with that of Table 4 of Maurya et al [25] where they have prepared the table for the value of n = 3.3 only for different compact stars whereas in the present study our table includes a wide range of n = 3 to n = 10,000.…”
Section: Discussionmentioning
confidence: 90%
“…It is to further noteworthy that this low value surface redshift is not at unavailable in the literature where Shee et al [43] obtained a numerical value for Z as 0.30 (also see Refs. [12,[44][45][46][47] for a low value surface redshift).…”
Section: Discussionmentioning
confidence: 99%
“…A tally of this value with the already available data set immediately reveals that the star is nothing but either a quark/strange star (see Table 1 of the Ref. Bhar et al (2015)) or a brown dwarf star of type F5 (see the Link: http://www.world-builders.org/lessons/less/les1/StarTables.html).…”
Section: Nature Of the Starmentioning
confidence: 90%
“…Ray et al (2008), Rahaman et al (2010aRahaman et al ( ,b, 2014Rahaman et al ( , 2015b, Usmani et al (2011) andBhar (2014). In this line of investigations some special mention are of the very recent works of Rahaman et al (2015a) and Bhar et al (2015). Search for a new wormhole solution inspired by noncommutative geometry with the additional condition of allowing conformal Killing vectors was performed by Rahaman et al (2015a) whereas Bhar et al (2015) have shown that a new class of interior solutions for anisotropic stars are possible by admitting conformal motion in higher-dimensional noncommutative spacetime.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation